Azerbaijan Republic : Report on Observance of Standards and Codes-Fiscal Transparency Module-Update. (IMF Staff Country Reports; Country Report ;, 2003)
This paper presents an update to the Report on Observance of Standards and Codes on Fiscal Transparency Module for Azerbaijan. Reforms aimed at delineating the roles of the public and private sector in Azerbaijan have moved forward, but a significant amount of work still lies ahead. During 2002, the government simplified requirements for business licensing in an effort to strengthen private sector development. Important steps were also taken toward clarifying the relationship between the government and state-owned enterprises.